CaloriSMART: Small-scale test-stand for rapid evaluation of active magnetic regenerator performance. (1st November 2019) - Griffith, Lucas; Czernuszewicz, Agata; Slaughter, Julie; Pecharsky, Vitalij
Highlights: A system using a compact, 5 mL total volume active magnetic regenerator is reported. Performance is demonstrated for maximum magnetic field strengths of 1.13 and 1.45 T. The system achieves specific exergetic cooling power of. 73 W L - 1 T - 1 Exergetic cooling power scales with applied magnetic power. A new performance metric – exergetic power quotient – is proposed. Abstract: We report operation of a device designed specifically for rapid experimental evaluation of performance of magnetocaloric materials in different magnetic fields using a compact active magnetic regenerator bed with a total volume of approximately 5 mL. Other features of the system include digital control of the rotating-permanent-magnet field source and custom dual-opposed syringe pump that enable precise tuning and coupling of the flow profile and the magnetic field profile. Performance of the device is demonstrated for flow volumes between 1 and 4 mL (utilization from 0.48 to 1.9), maximum magnetic fields of 1.13 and 1.45 T, and applied cooling powers from 0 to 20 W at frequencies from 0.5 to 4 Hz. A regenerator comprised of 25 g of 200 µm spherical Gd powder reached temperature spans of 19.3 K under no applied cooling load and 2.6 K under the maximum applied cooling load of 20 W. The device also achieves a very high specific exergetic cooling power of 73 W L −1  T −1 . Results obtained at two different maximum magnetic fields in the same device suggest a powerful new scaling for regenerator performance: the exergetic power quotient. The exergetic power quotient shows a simple scaling of device cooling performance with the amount of active material and the magnetic field strength. This suggests results from a small device correlate to expected performance of a larger regenerator, making the exergetic power quotient a well-suited parameter for evaluating functionality of active magnetic regenerators employing new magnetocaloric materials.